Mathematical modelling of sustainable procurement strategies: three case studies - Gergin, Zeynep; AKTİN, AYŞE TÜLİN (Journal of Cleaner Production, 2016)
Sustainable procurement is the process of meeting the needs of an organisation with the most beneficial monetary value, while mitigating the diverse effects of its operations on society and environment. There are studies which adopt environmental criteria to procurement decisions, whereas, works integrating the three dimensions and discussing the trade-offs between them are scarce. In this paper, the three dimensions of corporate sustainability; environmental economical social, are integrated into supplier selection and demand allocation decisions. With their integrated approach, the proposed mathematical models aim to contribute to the relevant literature by analysing different sustainable procurement strategies. Initially a questionnaire is introduced for measuring the sustainability scores of a company's potential suppliers, and these scores are then used as an input to the models. The developed mixed integer linear programming models distribute demand to the most sustainable firms in the supplier pool of the company, while ensuring minimum procurement cost for the identified strategy. The questionnaire and models are implemented in three companies to interpret the outcomes of different sustainability strategies on the procurement decisions. Selection of the most appropriate strategy is a managerial decision influenced by the varying dynamics of the company and the market conditions. These models demonstrate an easy and practical approach in assisting sustainable procurement. Results are promising in displaying the trade-offs between the sustainability dimensions of different strategies with alternating procurement costs, and can aid the managers to integrate environmental, economical, and social aspects into their supply chain operations. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Sustainable procurement; Mathematical modelling; sustainability; Triple-bottom-line; Supply Chain Management; Of-The-Art; Environmental-Management; Performance; Selection; Collaboration; Operations; Framework; Criteria; Industry